Zinner Syndrome in Pediatric Age: Issues in the Diagnosis and Treatment of a Rare Malformation Complex - Cascini, Valentina; Di Renzo, Dacia; Guerriero, Vittorio; Lauriti, Giuseppe; Lelli Chiesa, Pierluigi (Frontiers in Pediatrics, 2019)
Zinner syndrome (ZS) is the association of congenital seminal vesicle cysts and ipsilateral upper urinary tract anomalies, such as multicystic displastic kidney (MCDK). This condition is rare in pediatric age and both diagnosis and treatment are challenging. The aim of this study was to analyze the issues in diagnosis, management, and treatment of ZS in pediatric age. The medical records of two patients with ZS were examined. Furthermore, a review of the literature on this topic in pediatric age was performed. In our experience the diagnosis of ZS was incidentally achieved in the first months of life, as a consequence of studies performed for a prenatal diagnosis of MCDK. The first patient presented unspecific and transient symptoms, the second infant was completely asymptomatic. They were conservatively treated, with a long-term follow-up planned at least until adolescence. Fifty cases of ZS in pediatric age have been reported in the literature up to now. Only 12/50 were diagnosed in the first year of life. The diagnosis was demanding, as the clinical presentation was unspecific and the results at imaging studies needed a differential diagnosis with other retrovesical masses. More than 80% of these cases were asymptomatic at long-term follow-up. Therefore, a conservative management of ZS has been accepted for asymptomatic or poorly symptomatic patients, with occasional, transient, and unspecific symptoms, such as urinary tract infections or orchyepididimytis. As the surgical management is challenging, it is proposed only in those symptomatic patients. In conclusion, ZS is rare in pediatric age. However, it should be considered in the differential diagnosis of cystic masses within the pelvis in males with ipsilateral renal anomalies. A conservative treatment with a long-term follow-up is a safe option in the management of asymptomatic or poorly symptomatic patients, thus reserving the surgical approach only in those cases with symptoms.